INTERVENTION CONVENTIONAL IN OVERCOME PROBLEMS BREAST SWELLING IN BREASTFEEDING MOTHERS : OVERVIEW SYSTEMATIC - Christina Cahyani; Imami Nur Rachmawati (Jurnal Ipteks Terapan, 2023)
Introduction : Breast engorgement is the most common problem experienced by breastfeeding mothers , which appears on the day second to fourth post labor . If the problem of swelling is not treated immediately, then will impact on milk production . Method : Do review systematically on 1046 articles various intervention conventional method that can be applied in the treatment unit with using an international database such as : SAGE, Proquest , EMBASE, Taylor & Francis, and succeeded found ten intervention conventional in overcome breast swelling . Purpose : Identify various intervention conventional in overcome problem swelling of the breasts in nursing mothers in the treatment room . Result: Deployment non- pharmacological intervention proven effective overcome swelling of the breast and pain in the breast in the treatment room on an average day third and fourth (P=0.000 – 0.001; Ci 95 %). Participants who get education with therapy conventional own higher odds _ For provide exclusive breastfeeding . Recommendation : Intervention conventional effective reduce breast swelling , breast tenderness and increase exclusive breastfeeding _ during is at treatment room . Application education breast-feed with gift therapy Conventional medicine is very beneficial for breastfeeding mothers in the treatment room.